Machine Learning Classification for Blood Glucose Performances Using Insulin Sensitivity and Respiratory Scores in Diabetic ICU Patients - Abdul Razak A.; Partan R.U.; Razak N.N.; Abu-Samah A.; Nor Hisham Shah N.; Hasan M.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Blood; Classification (of information); Glucose; Insulin; Intensive care units; Motion compensation; Nearest neighbor search; Oxygen; Respiratory system; Blood glucose; Blood glucose performance; Classification models; Diabetes mellitus; F-score; Insulin sensitivity; Machine learning classification; Performance; Respiratory failure; Respiratory score; Machine learning